2005
DOI: 10.1016/j.yexcr.2005.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress and shear rate differentially affect the multi-step process of leukocyte-facilitated melanoma adhesion

Abstract: Previous studies have shown that neutrophils (PMNs) facilitate melanoma cell extravasation [M.J. Slattery, C. Dong, Neutrophils influence melanoma adhesion and migration under flow conditions, Intl. J. Cancer 106 (2003) 713-722] Little is known, however, about the specific interactions between PMNs, melanoma and the endothelium (EC) or the molecular mechanism involved under flow conditions. The aim of this study is to investigate a "two-step adhesion" hypothesis that involves initial PMN tethering on the EC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 40 publications
5
78
0
Order By: Relevance
“…In addition, constitutive secretion of the chemokine IL-8 from melanoma cells, as well as the capacity of increased IL-8 production from a melanoma-PMN microenvironment, was significantly decreased following inhibition of mutant V600E B-Raf. Coupling these observations with previous studies showing that endogenously produced IL-8 and ICAM-1-h 2 integrin binding mediate melanoma extravasation (11,12) provides a rationale and mechanistic basis for targeting mutant V600E B-Raf to inhibit melanoma extravasation and subsequent metastasis development. Scott Simon, University of California Davis, Davis, CA) and were maintained in culture as previously described (17).…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…In addition, constitutive secretion of the chemokine IL-8 from melanoma cells, as well as the capacity of increased IL-8 production from a melanoma-PMN microenvironment, was significantly decreased following inhibition of mutant V600E B-Raf. Coupling these observations with previous studies showing that endogenously produced IL-8 and ICAM-1-h 2 integrin binding mediate melanoma extravasation (11,12) provides a rationale and mechanistic basis for targeting mutant V600E B-Raf to inhibit melanoma extravasation and subsequent metastasis development. Scott Simon, University of California Davis, Davis, CA) and were maintained in culture as previously described (17).…”
Section: Introductionsupporting
confidence: 62%
“…Previous studies have shown that human PMN facilitates melanoma extravasation in vitro (11,12). To investigate the interaction of melanoma cells with mouse PMNs, colocalization of green GFP-tagged melanoma cells and red phycoerythrin-tagged mouse PMNs in the lungs was studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that V600E B-Raf plays a critical role regulating both of these processes thereby regulating metastasis. Interaction of melanoma cells with neutrophils facilitates attachment to the endothelium, thereby promoting extravasation into lung stroma (52,53). We have provided novel insight into these processes showing that, in melanoma, V600E B-Raf promotes metastasis by facilitating extravasation across the endothelial layer under flow conditions and by conferring increased proliferative potential in the lung microenvironment.…”
Section: Discussionmentioning
confidence: 98%
“…B-Raf enhanced extravasation by facilitating interaction with neutrophils, which aided in tethering the melanoma cell to the endothelial lining under flow conditions, thereby promoting movement of the melanoma cell through the endothelial lining (52,53). Once extravasation has occurred into lung stroma, cells need to proliferate, also facilitated by V600E B-Raf.…”
Section: V600ementioning
confidence: 99%